Function of nurses and other staff to minimize hospital waste in selected hospitals in Isfahan - Maroufi, Maryam (Medknow Publications & Media Pvt Ltd, 2012)
CONTEXT: Medical waste (MW) is all waste materials generated at health care facilities. MW naturally is hazardous for environment and subsequently for human. Waste minimization (WM) is the latest alternative for risk reduction. All hospital staff generally and nurses specially can play an active role through education and the implementation of measures to reduce medical wastage and their environmental effects. AIMS: This study is aimed to compare nurses and other staff functions in selected hospitals in Isfahan about waste minimization strategies. SETTINGS AND DESIGN: This is a descriptive analytical study. The study tool was a researcher -designed questionnaire in five area of waste minimization based on WHO recommendation. MATERIALS AND METHODS: There were 90 nurses and other staff from randomized selected public and private hospitals of Isfahan as the sample of this research. This study was done in 2009. STATISTICAL ANALYSIS USED: Data were analyzed by t-test using SPSS(16). RESULTS: Nurses mean score of WM performance was 58.16 (12), and others was 58.56 (12.18) (of max 100). There was no significant difference between nurses and others mean score of WM performance according to t-test. There was not significant difference between WM performances of two studied groups in public and private hospitals based on t-test. Comparing between two studied groups mean scores by waste minimization areas indicated that nurses have done significantly better in source reduction area and other staffs have acted better in waste segregation (P < 0.05). CONCLUSIONS: All of hospital staff specially, nurses have an important role in qualified waste management practice of hospitals. Totally mean score of WM performance in hospitals (nurses and other) was average. With regard to other countries activities, this result is disappointing. So, it is necessary to plan educational programs for hospital staff, especially nurses.